BRAND ATTACHMENT, BRAND EXPERIENCE, BRAND IMAGE, PERCIEVED QUALITY, PERCEIVED VALUE, AND BRAND LOYALTY - Ahmadian, Sahar; Sahraei, Bashir; Khosro, Shekoufeh Khojasteh (Transpublika Publisher, 2023)
This research investigated the relationship between brand attachment, brand experience, and brand image, and their influence on perceived quality, perceived value, and brand loyalty, with a specific focus on the Mashhad Leather brand in Iran. Employing an applied and descriptive research approach, the study utilized a comprehensive survey method facilitated by a standard questionnaire to gather data from a diverse group of 386 Mashhad Leather consumers. Leveraging the SmartPLS software for rigorous analysis, the study uncovered several crucial findings that shed light on the dynamics between the aforementioned variables. The results underscore the substantial impact of brand attachment, brand experience, and brand image on the perceived quality of Mashhad Leather products, highlighting the significance of emotional and experiential connections in shaping consumer perceptions. Additionally, the study reveals a robust correlation between perceived quality and perceived value, indicating that consumers' judgments of product excellence significantly shape their assessment of the brand's worth. Notably, the research findings establish perceived value as a key driver of brand loyalty, emphasizing the pivotal role it plays in fostering enduring customer-brand relationships.